A case report on disseminated tuberculosis in the setting of coronavirus disease 2019: cause or consequence?. Issue 3 (10th September 2022) - Khataniar, Himsikhar; Sunil, Diya; AV, Lalitha
Abstract: Tuberculosis (TB) is a deadly infection that can lead to disseminated disease in children <15years of age exhibiting risk factors such as low host immunity, concurrent infection(s), and/or malnutrition. A case involving a 14-year-old boy diagnosed with disseminated tuberculosis is reported. On investigation, the patient was positive for coronavirus disease 2019 (COVID-19) antibodies, GeneXpert (Cepheid, Sunnyvale, CA) positive for TB with multisystem involvement, lymphopenia, and highly elevated inflammatory markers, indicating multisystem inflammatory syndrome in children (MIS-C) and disseminated TB. The patient was started on antitubercular treatment (ATT), steroids, and supportive treatment. His condition improved over the ensuing few days, and he was discharged with ATT and antiepileptics. Although a few studies involving adults have established a connection between the progression of TB and COVID-19, this case report establishes a similar clinical picture in a child, which has not yet been reported.